Estudos dos processos digestivos proteolítico e amilohidrolítico de juvenis de pacu Piaractus mesopotamicus (Holmberg, 1887), alimentados com níveis crescentes de proteína - Visentainel, Joyce (2008)
The knowledge on digestive enzymes allows understanding same aspects of animal nutritional needs and dietary components effects on the activity of those enzymes. Considering the lack on the information about proteolytic and enzymes from the gut wall versus digesta in P.mesopotamicus, it is interesting to see the behavior, distribution and production dynamic of those enzymes. Initially the investigation of digestive processes was proposed in the gut wall and digesta of pacu juveniles over distinct time intervals (0,5; 2; 6; 12 and 24 hours) following the last feeding. At a second time, the digestive aspects in the wall and digesta of pacu were investigated in fish fed with four levels of crude protein (20, 26, 32 and 38%). The digestive, unespecific-proteolytic enzymes, trypsin, chymotrypsin and amylase were assayed in all sections of digestive tract (stomach, piloric cecae, foregut and hindgut) in the first and in the second experiment. The results from the first experiment have shown that pacu presents digestive enzyme activity from the post-prandial moment until 24 hours post-feeding, either in the gut wall or in digesta. However, such enzymatic activity is much differentiated, either to different enzymes types or to different gut sections. In the second experiment our results have shown that digestive amylase and proteases were responsive to the levels of dietary carbohydrate and protein. Moreover, the enzymatic secretion may be direct or conversally proportional to specific substrat of diet and dependent on the enzyme and the gut section. In conclusion the protein production is impaired by fasting longer than 12 hours and the enzyme gut content from all gut is not emptied in consequence of feeding. The alkaline protease content is proportional to its gut wall content. The digestive enzyme of pacu are induced by dietary protein and carbohydrate concentrations.